Mitigasi Sick Building Syndrome Pada Rumah Deret Studi Kasus: Rumah Di Perumahan Puri Wirokerten, Bantul - Ciptoleksono, Eka (Syntax Literate, 2026)
Sick Building Syndrome (SBS) is a condition caused by poor indoor air quality, affecting the health of building occupants, including respiratory problems and discomfort. In Indonesia, this issue is becoming increasingly relevant in row housing areas with limited land and poor ventilation management. This study aims to identify the causes of SBS in row houses at Puri Wirokerten Asri (PWA) and design a mitigation concept that improves indoor air quality. A qualitative approach with descriptive analysis of the building conditions and indoor air quality was used. The results indicate that the main causes of SBS in PWA’s row houses are insufficient natural ventilation and construction defects that cause poor air circulation. Proposed mitigation solutions include improving cross-ventilation systems and renovating buildings to enhance air circulation. This study is expected to contribute to the design of healthier and more habitable row houses, improving residents' quality of life by creating a cleaner and more comfortable environment.